Mrs. Zarktourni's Numb and Tingly Feet: A Metabolic Syndrome Workshop - Amina Sadik; Paul Kalekas; Csaba Fulop; Vladimir Bondarenko (Association of American Medical Colleges, 2015)
Abstract Introduction This metabolic syndrome case was written to illustrate the connections between a lifestyle change involving nutrition and a sedentary life, and the consequent comorbidities. Since this case is presented towards the end of the medical biochemistry course in our first-year medical curriculum, several metabolic pathways are revisited and the interactions between them are mapped, thereby showing an overall effect on different organs in the human body Methods This clinical-based workshop takes approximately 2 hours. The majority of the session is spent on the final discussion of the case with each group where students are given the opportunity to ask clarifying questions. The session concludes with a 15-minute individual case quiz that consists of 10 multiple-choice questions. This case can be implemented in different teaching approaches such as problem-based learning, team-based learning, or, in our case, concept mapping workshops, and any hybrids thereof. Results Our data from the quiz and exam questions related to this material suggest that the concepts illustrated by this case were well understood by students. The average score of the attached case quiz was 83%. The case-related material was also tested in three questions on the unit 4 exam, and students scored 81%, 98%, and 98%, respectively, while the overall average of the unit exam was 81%. These data indicate that students effectively retained and applied their knowledge of this case. Discussion The prevalence of obesity and associated comorbidities in developed countries is a growing concern for the medical community. This case comprehensively connects biochemical concepts to the importance of nutritional choices in order to provide a thorough understanding of the causes and prevention of the obesity epidemic. This acquired knowledge enables future physicians to educate their patients and their communities.